Hubungan Antara Kepatuhan Wajib Pajak dan Penerimaan Negara: Perspektif Ekonomi Publik - Viona, Merry; N, Nabila; Katanging, Deva Garcia; Pangestoeti, Wahjoe (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the relationship between taxpayer compliance and national revenue, and its impact on the country’s economy. Data obtained through interviews and document analysis show that a high level of tax compliance directly contributes to increased national revenue. Higher tax revenue enables the government to fund infrastructure projects, education, and other social sectors that support economic growth. Factors affecting tax compliance, such as tax education, government oversight, and incentives or penalties, were also found to play an important role in improving compliance levels. This study suggests that the government should improve the transparency of tax usage, strengthen oversight, and provide incentives for compliant taxpayers to maximize national revenue and promote sustainable economic development.